Digitizing Zakat Distribution in Malaysia: A Case Study on Application Process at Kedah State Zakat Board - Nor, Shifa Mohd; Yaacob, Salmy Edawati; Rahman, Aisyah Abdul; Zainal, Hafizah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This research examines the implementation of the digital zakat application process for eligible recipients via the "Zakat on Touch" (ZoT) platform, managed by the Kedah State Zakat Board (LZNK), Malaysia. Amidst technological advancements, the LZNK has introduced the ZoT application to facilitate zakat transactions. Although this system offers a range of features that benefit zakat contributors in Kedah, it has yet to implement the digitalization of the application process. This study evaluates the potential for incorporating a zakat application functionality within the ZoT system. The methodology adopted for this research includes in-depth interviews with seven LZNK officials. The findings suggest that, with proposed enhancements currently under evaluation, the ZoT application could facilitate the online zakat application process for eligible recipients. Moreover, LZNK's adept implementation of digital solutions has markedly improved the zakat management system, benefiting the payers, beneficiaries, and administrators. The community's favorable response to these initiatives is evidence of LZNK's successful innovation in innovating zakat management practices within Kedah.This research makes a significant contribution to knowledge fourfold.  First, to reveal the zakat management models used in various countries, which are valuable benchmarks and indicators for the development of digital zakat. Second, the importance and need for increased use of technology in Malaysia, especially focusing on the competence of zakat institutions in the field of financial technology through the LZNK case study.  Third, the findings of this research found that the positive impact of digital zakat in the state of Kedah is greater than the negative impact.